2014
DOI: 10.1016/j.ijnonlinmec.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A linear complementarity problem formulation for periodic solutions to unilateral contact problems

Abstract: Presented is an approach for finding periodic responses of structural systems subject to unilateral contact conditions. No other non-linear terms, e.g. large displacements or strains, hyper-elasticity, plasticity, etc. are considered. The excitation period due to various forcing conditions-from harmonic external or contact forcing due to a moving contact interface-is discretized in time, such that the quantities of interest-displacement, velocity, acceleration as well as contact force-can be approximated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…The aforementioned developments are recalled for the sake of completeness as they have already been widely used in the literature [14] for various types of nonlinearities. Nonetheless, when considering the HBM with contacts nonlinearities, it has been shown that it is prone to the Gibbs phenomenon [13] and, as a result, performs poorly [7].…”
Section: Specific Developments For Blade-tip/casing Contactmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned developments are recalled for the sake of completeness as they have already been widely used in the literature [14] for various types of nonlinearities. Nonetheless, when considering the HBM with contacts nonlinearities, it has been shown that it is prone to the Gibbs phenomenon [13] and, as a result, performs poorly [7].…”
Section: Specific Developments For Blade-tip/casing Contactmentioning
confidence: 99%
“…Secondly, conclusions drawn from published experimental studies put forward that witnessed interactions are often related to transient or diverging motions which may not be captured with frequency-domain approaches. Thirdly, while frequency-domain approaches are often viewed as more computationally efficient than time integration methods, they still represent a computational challenge when applied to complex mechanical systems with a large number of nonlinear degrees of freedom (dof), even more so when one of the two impacting structures is assumed to be perfectly rigid [7]. For all these reasons, most of the published numerical work that was compared to experimental observations relied on time integration methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linear complementarity problem (LCP) is a problem of the form y = Mx + b, y ≥ 0, x ≥ 0, and y x = 0, where M is an × matrix and x, y, and b are an -dimensional vector [8]. LCP equations may have unique solution, no solution, or multiple solutions.…”
Section: Linear Complementarity Problemmentioning
confidence: 99%
“…Nonsmooth methods have been succesfully applied in a variety of contexts ranging from granular media (Renouf et al, 2004), geomaterials (Jean, 1995), multibody dynamics (Chen et al, 2013) to realistic simulations of hair motions and living systems (Acary et al, 2014;Bertails-Descoubes et al, 2011). In the field of vibration, the method has been applied to rotor/casing contacts in (Meingast et al, 2014) as well as to string vibrations in (Ahn, 2007), where the study was however limited to the case of a perfect string without stiffness and a frictionless contact. In the area of musical acoustics, the action of a grand piano has been recently simulated efficiently by using a nonsmooth approach (Thorin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%